Kajian rintis penilaian status pemakanan di kalangan pesakit onkologi pediatrik di Hospital Universiti Kebangsaan Malaysia - Noor Aini Mohd Yusoff,; Zalina Abu Zaid,; Raiza Sham,; Rosita Jamaludin,; Suzana Shahar,; A. Rahman A. Jamal, (penerbit ukm, 2007)
Malnutrition is common among pediatric oncology patients. Factors contributing to malnutrition include physiological abnormalities, response to the tumors and side effects of the treatment. A pilot study was carried out to determine the nutritional status of 17 pediatric oncology patients aged 4 to 12 years old in Hospital Universiti Kebangsaan Malaysia, Kuala Lumpur. The nutritional status was assessed via anthropometric measurements and dietary intake through 3 days repeatitive 24 hours diet recall with subjects and their carers. Biochemical profiles (serum albumin and hemoglobin) were reviewed from the medical record. Through anthropometry measurements, weight and height were used to calculate Z-scores and further determine the percentile weight-for-age, height-for-age using NCHS percentile charts (WHO 1983).Frisancho’s standards (1981) were used to define malnutrition based on MUACfor-age. Underweight as determined using z scores below -2 for weight-for-age was observed in 70.6% of the subjects. Whilst, 76.5% of the subjects were classified as stunted (z score < –2) for height-for-age. Based on MUAC-for-age percentile, the sign of severe malnutrition category (<5 percentile) was observed in 35.3% of the subject and 23.6% of the subject were in the moderate malnutrition (>5 – <10 percentile). About 70.6% of the subject had low haemoglobin (< 11 g/dl) and 29.4% of the subject were hypoalbuminemia(< 35 g/dl) . Total macronutrient intake was assessed and compared with the individual requirement (Seashore 1984) for energy and protein intake were satisfactory, except for subjects in age group 10 – 12 years who achieved only 70% of the individuals requirements. As a conclusion, although food intake of the subjects was satisfactory but chronic malnutrition was prevalent. Early recognition of malnutrition is essential in order to plan for a nutritional intervention and further enhancing the quality of life.